Characterization of Tannic Acid Chemically Crosslinked PVA Chitosan Hydrogel - Nana Nurindah Upara; Muhammad Taupik; Multiani S Latif; Nur Rasdianah; A. Mut’hi Andy Suryadi (Jurnal Literasi Mandiri, 2026)
Hydrogel is a hydrophilic material that can absorb and retain large amounts of water through the formation of hydrogen bonds between polymer functional groups to form a stable three-dimensional network. The physicochemical characteristics of hydrogels are greatly influenced by the cross-linking process that determines the network density and stability of the preparation. This study aims to determine the effect of variations in the concentration of tannic acid as a chemical crosslinker on the physicochemical characteristics of polyvinyl alcohol (PVA)-chitosan-based hydrogels. Hydrogels were formulated with varying concentrations of tannic acid of 1%, 3%, and 5%, then evaluated including organoleptic tests, pH, viscosity, spreadability, adhesion, swelling index, irritation test, and characterization using Fourier Transform Infrared (FTIR). The results showed that increasing the concentration of tannic acid caused the formation of a denser hydrogel network, which was characterized by a decrease in the swelling index value and an increase in adhesion and changes in viscosity. The pH values ​​of all formulas were within the physiological pH range of the skin. Irritation tests on 20 panelists showed that all formulas did not cause irritation reactions. FTIR analysis confirmed the presence of molecular interactions between PVA, chitosan, and tannic acid through hydrogen bond formation. Overall, variations in the concentration of tannic acid as a chemical crosslinker affected the physicochemical characteristics of the PVA–chitosan hydrogel and resulted in stable preparations with good quality